Fracture Toughness of Porous Material of LSCF in Bulk and Film Forms. Issue 7 (20th March 2015) - Chen, Zhangwei; Wang, Xin; Giuliani, Finn; Atkinson, Alan; Faber, K. T.
<x xml:space="preserve">Abstract</x> Fracture toughness of La0.6Sr0.4Co0.2Fe0.8O3‐δ (LSCF) in both bulk and film forms after sintering at 900°C to 1200°C was measured using both single‐edge V‐notched beam (SEVNB) 3‐point bending and Berkovich indentation. FIB/SEM slice‐and‐view observation after indentation revealed the presence of Palmqvist radial crack systems after indentation of the bulk materials. Based on crack length measurements, the fracture toughness of bulk LSCF specimens was determined to be in the range 0.54–0.99 MPa·m1/2 (depending on sintering temperature), in good agreement with the SEVNB measurements (0.57–1.13 MPa·m1/2). The fracture toughness was approximately linearly dependent on porosity over the range studied. However, experiments on films showed that the generation of observable indentation‐induced cracks was very difficult for films sintered at temperatures below 1200°C. This was interpreted as being the result of the substrate having much higher modulus than these films. Cracks were only detectable in the films sintered at 1200°C and gave an apparent toughness of 0.17 MPa·m1/2 using the same analysis as for bulk specimens. This value is much smaller than that for bulk material with the same porosity. The residual thermal expansion mismatch stress measured using XRD was found to be responsible for such a low apparent toughness.